Design, facile synthesis, spectroscopic characterization, and medicinal probing of metal‐based new sulfonamide drugs: A theoretical and spectral study. (12th October 2020) - Hassan, Abrar U.; Sumrra, Sajjad H.; Raza, Muhammad A.; Zubair, Muhammad; Zafar, Muhammad N.; Mughal, Ehsan U.; Nazar, Muhammad F.; Irfan, Ahmad; Imran, Muhammad; Assiri, Mohammed A.
Abstract : Sulfonamide core‐based new ligands 4‐{[(2, 4‐dihydroxyphenyl)methylidene]amino}benzene‐1‐sulfonamide as (L 1 ) and 4‐[(2, 4‐dihydroxyphenyl)methylidene]amino‐ N ‐(5‐methyl‐1, 2‐oxazol‐3‐yl)benzene‐1‐sulfonamide as (L 2 ) have been synthesized through condensation response and were characterized by their UV–Vis, FT‐IR, 1 H NMR, 13 C NMR, mass spectrometry, and elemental analyses. The ligands were reacted with transition metals (V, Fe, Co, Ni, Cu, and Zn) to synthesize the metal complexes (1 )–(12 ). The metal complexes were also characterized, based on their physical (color, solubility, yield and melting point, conductance, magnetic), spectral (UV–Vis, FT‐IR, LC–MS), and microanalytical (elemental) data. The bidentate ligands were coordinated with transition metal salts by exploiting the azomethine nitrogen and the hydroxyl group oxygen. The electronic spectra for the metal complexes suggested them to have square‐pyramidal geometry for their vanadyl complexes whereas all the remaining complexes to be octahedral. The optimized geometries of the ligands at their ground state energies were studied through density functional approach at the B3LYP/6‐31G** level. The electronic, molecular electrostatic potential (MEP), and chemical descriptive properties were also explored by first‐principle insights. A clear intramolecular charge transfer was witnessed by occupied molecular orbitals (HOMO) to unoccupied molecular orbitals (LUMO). In addition, all the products were then tested for their antimicrobial potential against four bacterial ( Staphylococcus aureus, Bacillus subtilis, Escherichia coli, and Klebsiella pneumoniae ) and two fungal ( Aspergillus flavus and Aspergillus niger ) species. The synthetic products were also tested for their antioxidant and enzyme inhibition properties that gave the excellent results implying their bioactive nature. The screening results revealed the metal complexes to have enhanced bioactive actions in comparison with their respective ligands. Abstract : Sulfonamide‐based two novel ligands and their transition metal complexes have been synthesized and characterized. The ligands undergone through density functional theory (DFT) analysis to understand their bioactivity likeness. All the synthesized products were screened experimentally for their medicinal properties to find their good to excellent bioactive nature.